THE BIOLOGICAL BASIS OF THE MANIFESTATION OF LEFT-HANDEDNESS. HEREDITY (Education in the 21st Century, 2023)
At all times of human development, leftists have aroused special interest and careful attitude in a certain part of society. Left-handedness has been a mystery for centuries, which has not yet been fully revealed. There is still no clear answer to the question of what is the cause of left-handedness, what is the difference between right-handers and left-handers.Left-handedness cannot be considered a cause of developmental disorders or abnormalities, reduced mental and physical abilities. The dominance of the leading hand depends not on the child's "will" or his persistence, desire, but on the hemispheric activity of the brain.With great effort, a left-handed child can be taught to work with his right hand, but his biological nature cannot be changed.The problem of the origin of leftism in pedagogy is not a priority problem, as pedagogy studies the manifestation of an already existing phenomenon in the processes of socialization of the educational person: adaptation, disengagement.Given the social adjustment of left-handed children, special attention should be paid to the psychophysiological characteristics of the child, in particular, the hemispherical asymmetry of the brain.